Development of an online intervention to increase mental health literacy and promote self-management of depression in university students - Davies, Eleanor Bethan (2015)
Mental health literacy encompasses an individual’s knowledge and attitudes which influence recognition, treatment and management of a mental health problem. Depression is a common mental health problem experienced by university students, but they often do not seek professional help for their mental health, and prefer more informal sources of help. Online interventions to improve students’ mental health literacy could be a useful and engaging mental health promotion strategy in this population, in order to help improve their recognition and appraisal of depression, their ability to respond to it appropriately (either through seeking professional help or applying self-help), and improve their ability to support others experiencing depression. This thesis describes four studies conducted to inform the development of an online mental health literacy intervention tailored for Nottingham-based university students. These studies describe: 1) a systematic review and meta-analysis of website-based interventions for common mental health problems in university students; 2) a survey-based study investigating the profile of depressive, anxiety and hypomanic/manic symptomology in local students; 3) an interview-based study with students about their mental health and well-being since entering university, and their perspectives about help-seeking and self-management; and 4) an exploratory study investigating students’ mental health first aid skills for a hypothetical friend experiencing depression. This, coupled with literature review of student mental health, mental health help-seeking, and mental health literacy, resulted in the development of the pilot online intervention (“Managing Your Mood Online”), which underwent usability testing with a sample of representative end users. This study found the pilot intervention to be acceptable and usable, but with many potential areas for improvement. This thesis concludes with several considerations for future development of the online intervention.